E-Learning in Vocational Business Education during Covid-19 Pandemic in Nigeria; Challlenges, Benefits and Way Forward - Ayo Abel Oghenebrorhie; Diavwoderu Happy Aghogho; Okifo Joseph (Journal of Vocational Education Studies, 2022)
During Corona Virus (Covid-19) lockdown, the introduction of the use of various applications such as zoom and the likes were on high side. Teachers were able to teach from their homes to the students in their respective homes. Unfortunately because of the economy of Nigeria, not everyone has the financial capacity to acquire phones, laptops and other related ICT tools to enable all to participate in the online teaching – learning process, in fact when it comes to adequate usage of ICT products, Nigeria is still far behind; only few are versatile in the use of ICT tools. The corona-virus is seen as the most trying time in the history of mankind. This period prompted concerned personnel and government to give more attention to the alternative to physical teaching-learning process called e-learning; audio, audio-visual, virtual learning and all forms of nonphysical contact teaching – learning process were more utilized. Though as good as it was, this exposes the major strength and huge weakness of the system owning to the fact very many things still need to put in place to take e-learning in Nigeria to its supposed place in the developmental trend of the world at large. This paper examined concept of E-Learning, historical development of E-learning, E-learning during COVID-19, disruptions of COVID-19 in Nigerian Educational Sector, challenges associated with E-Learning in Business education and benefits of E-Learning during COVID-19 pandemic in business education programmes.